Equidade no uso dos centros de especialidades odontológicas do Nordeste: análise do 2° ciclo do PMAQ-CEO - Lira, Gabriela de Nazaré Wanderley (2021)
Introduction: Equity, ideally, requires that people have fair opportunities to reach their health potential and that no one should be less favored to reach that potential. To understand the functioning of oral health services with the principle of equity is essential to recognize the specific factors that contribute to the increase and perpetuation of inequities in oral health. Aim: To analyze the Dental Specialization Centers in the Northeast according to the principle of equity and its relationship with aspects of waiting list management and planning instruments. Methodology: Cross-sectional study involving 410 CEO who participated in the External Evaluation (AE) phase of the 2nd cycle of the PMAQ-CEO held in 2018, 4024 users and 367 municipalities in the Northeast. From the PMAQ-CEO data, scores were attributed to the users of the CEO according to their social vulnerability. The vulnerability of the CEO was measured from their users, and the municipalities according to the Social Vulnerability Index (IVS). In order to compare the vulnerability of the CEO with the municipal context in which the service is inserted, the indicator of the difference between the vulnerability of the CEO and the municipality was calculated, and so the CEO were ranked and allocated in quartiles according to the pro-inequity (PI) or pro-equity (PE) tendency in its use, resulting in 4 ordinal outcomes. Variables related to waiting list management, prioritization criteria and planning were used to build an explanatory model for the outcomes. The strength and the association effect between the independent variables and the outcomes were assessed using Odds Ratio, calculated by Ordinal Logistic Regression considering the global significance level of 5%. Results: Regarding vulnerability, 2.4% of CEO, 26.9% of users and 63.8% of municipalities were classified as having high or very high vulnerability. CEO who perform management of the waiting list and planning with epidemiological data were, respectively, 50,1 and 53,5% more likely to be in the worst outcome of the pro-inequity tendency (PI2). Conclusion: The study demonstrated that the principle of equity is incipient in the use of the CEOs of the Northeast and that the realization of the management of the waiting list and planning with epidemiological data, the way they are being performed, are potential amplifiers of the inequity in the service.